Lepton Pair-Production in Non-Commutative Standard Model with Polarized e$^{+}$e$^{-}$ Beams (Письма в ЭЧАЯ, 2024)
In this paper we study the lepton pair production with polarized electron - positron beam inthe context of non commutative standard mode(standard model extension in non commutativegeometry). Using the Seiberg-Witten map, we calculate the production cross-section to the first order in the noncommutative parameter θμν.. We consider the collision energy in the range 300-1000 GeV aproporiate to the future ILC collider energy ranges. We look at the angular distributiond dσ/dΩ and the total cross section to explore the noncommutativity of space-time effect at around Λ ∼ TeV and the possibility of observing these eect at ILC. It is shown that the deviation of the cross section angular distribution because of noncommutativity is signi -cant when Λ≈103 GeV. The total cross section of the lepton pair production is more sensitive to space - time deformation than that of unpolarized case, where we found that the deviviation in polarised case at ECM = 1000 GeV is about eight times as large as these in unpolarised case.